مفرداتِ قرآنی کی لغوی تحقیق: مولانا مودودی کی کاوشوں کا مطالعہ: A Lexical Investigation of Qur'ānic Phrases: A Study of Mawlānā Mawdūdī's Efforts (Al-Qamar, 2021)
Mawlānā Mawdūdi's services in the field of Quranic studies are valuable. This article studies his efforts regarding investigations of Quranic phrases. It finds that while doing lexical research of the words, he considered the composition of the Quranic words in terms of Arabic language, grammar and syntax, dictionaries, its uses in other places of the Quran and Sunnah Mutawātara. This is followed by contextualization while keeping in mind the comprehensiveness, because the same translation everywhere does not make the meaning clear. Thus, he successfully tried to adapt the meaning of verses in a clear way. His research of lexical investigations of Quranic Phrases helps a lot in understanding the Quran.
Keywords: Mawdūdī; Qur'anic Phrases; Lexical Investigation